Determinants Of Career Pathway Selection in Competency-Based Education - Kainyu, Fridah; Mwadulo, Mary; Munialo, Samson (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
In Competency-based Education (CBE), learners acquire skills and knowledge through a personalized and flexible learning path, based on their prior knowledge and skills. Selecting a career pathway is crucial and needs to be thought of carefully because of its long-term impact on an individual’s future career. With the implementation of competency-based education in Kenya, learners will need to choose from four career pathways before joining senior high school. Knowing the factors that may determine learners’ career pathway selection can be helpful in the development of strategies that may help them make informed decisions. In this study, data from 1575 teachers teaching Grade 7 and Grade 8 learners in 151 junior secondary schools in Meru County were analyzed, to determine the variables associated with career pathway selection using principal component analysis, linear regression analysis, correlation analysis, and factor analysis. An online survey was used to collect the data. The research tool was subjected to two domain experts to assess the content validity and also two domain experts to measure the face validity of the tool used. The average rating for face validity was 75% and content validity was rated at 70%. A pilot study of 100 junior secondary school teachers teaching Grade 7 and Grade 8 learners was conducted in Igembe North sub-county, in Meru County. A reliability test was done using SPSS to measure the Cronbach Alpha internal consistency of the instrument which was found to be 0.834%. Results showed that interest, performance, extracurricular activities, career goals, and the job market were critical factors in determining the career pathway selection of learners in competency-based education. The study provides insights into the factors determining career pathway selection among junior secondary school learners in Meru County. The study's results could inform policy aimed at improving competency-based education and helping learners make informed decisions about their future education and career paths.